PCR-mediated detection of Aspergillus species in bronchoalveolar lavage samples of febrile neutropenic patients with acute leukemias: Clinical results - Buchheidt, Dieter; Baust, Corinna; Skladny, H.; Baldus, M; Bräuninger, S.; Hehlmann, Rüdiger (Acute Leukemias IX, 2003)
The incidence of systemic fungal infections in neutropenic patients with malignant hematological diseases is increasing (Beck-Sague and Jarvis 1993; Bodey, Bueltmann, et al. 1992). Patients at highest risk for these life-threatening infections are those with prolonged periods of neutropenia after intensified chemotherapy, usually patients with acute leuke-mia or after bone marrow transplantation (Denning 1998). Particularly increasing are invasive infections with Aspergillusspecies, showing high mortality rates and, if the patient survives, also considerable complications often limiting further antileukemic therapies (Denning 1998). The paragon of antifungal therapy, Amphotericin B, is toxic; chemoprophylaxis against Aspergillus species is therefore controversially discussed and not generally recommended or practiced (Schwartz, Behre et al. 1999).4207
Gesehen am 16.05.2022